PENERIMAAN DIRI PADA WANITA “SINGLE PARENT” SURVIVOR KANKER PAYUDARA PASCA MASEKTOMI DI KOTA BEKASI - Sani, Silvia; Widya Nugraha, Andreas Corsini (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
This study aims to explore and explore more deeply how the description of the experience of self-acceptance in single parent women with breast cancer survivors after mastectomy. The method used in this research is qualitative with a phenomenological approach. This study involved two subjects and two significant others. Two of the subjects of this study were women who were diagnosed with breast cancer and had had a mastectomy. While the other two significant others are children of each subject. Methods of data collection using in-depth interviews, observation and documentation. This research is expected to be able to provide an overview of how the experience that has been passed by a subject who is a single parent as well as a breast cancer survivor and has done a mastectomy (breast removal) to be able to accept himself after a mastectomy which makes the subject lose his breasts. The description of self-acceptance that has been passed by the two subjects to be able to accept themselves as a whole and make the subject more optimistic in living life, among others: (1) rejection of the subject; (2) negative emotions, namely negative thoughts felt by the subject; (3) the subject's fear of seeing the condition of his own body; (4) the social support received by the subject; (5) the subject's adjustment; (6) the subject learns to love himself; (7) and finally the subject can accept himself as a whole (self-acceptance).